Penataan Tata Ruang Kantor Guru Pada SMA Negeri 63 Jakarta - Agus Tri Indah; Harun Al Rasyid (Universitas Bina Sarana Informatika, 2018)
One part of office management is office layout. Factors that determine success in conducting office activities is by way of preparation of workplaces and office equipment with the best. When viewed from the accuracy of office spatial election, this can determine the employee's comfort indirectly. Organizing office space is a necessity of today's modern offices. Arrangement of office layout provides added value for the continuity of organizational activities. Spatial arrangement is arrangement of all office machines, office equipment and office furniture in the right place, so that employees can work well, comfortable and free to move to achieve the goal of work. In this research mengobsevasi spatial arrangement of teachers of SMA 63 Jakarta, using qualitative descriptive research method, accompanied by data collection methods such as observation methods, interviews and documentation. The results of this study provide an overview of the spatial arrangement of teachers, namely most of the arrangement of the layout of teachers is in accordance with the theory. Spatial used teacher room is open with the arrangement of furniture and equipment efficiently, with short working principle, air temperature between 28 - 32 degrees Celsius, color selection of white room for bright effect, solar lighting system, as well as air circulation combination between AC and using a window equipped with air vents, but there are few drawbacks in the placement of some of the furniture and the type of open spaces, but this does not have a meaningful effect on the day-to-day activities of the teacher.